Mapping the Intellectual Structure and Thematic Evolution of Risk Management Research in SMEs: A Bibliometric Review - Yaman Suryaman (Entrepreneurship Faculty, Universitas Garut, 2026)
Small and medium-sized enterprises (SMEs) are very important for employment and economic development, but they still face a high level of exposure to financial, operational, technological, and environmental risks. This article is an attempt to give an overview of the intellectual landscape, main topics, and possible new challenges of SME risk management research. A bibliometric analysis was made with the help of 1, 105 articles indexed by Scopus and published between 1988 and 2026. Exploratory and correlative analyses were made of publication trends, source titles, countries, citations, author keywords, and thematic clusters. The findings reveal an impressive pace of growth especially after 2019, as more than half of the papers were written in the period 2020-2025. The discipline has a very high level of interdisciplinarity as shown by the involvement of 557 journals. Financial risk, credit risk, enterprise risk management, and performance are some of the major topics in the literature. The article identifies digitalization, resilience, sustainability, cybersecurity, and supply chain disruption as some of the new themes in the research. It is argued that SME risk management research has substantially evolved from being mainly focused on financial aspects to adopting a wider strategic perspective.